The 2009 Claremont Debates: The Promise and Pitfalls of Utilization-Focused and Empowerment Evaluation - Stewart I. Donaldson; Michael Q. Patton; David M. Fetterman; Michael Scriven (The Evaluation Center at Western Michigan University, 2010)
Background: Hundreds of evaluators visit the Claremont Colleges in southern California each year to discuss a wide range of topics related to improving the quality of evaluation practice. Debates between thought leaders in the field have been one of the most popular and informative ways to advance understanding about how best to practice evaluation in contemporary times. Purpose: The purpose of this article is to provide a written transcript of the 2009 Claremont Evaluation Debates. The first debate is between Michael Quinn Patton and Michael Scriven on the promise and pitfalls of utilization-focused evaluation. The second debate is between David Fetterman, Michael Quinn Patton, and Michael Scriven on the promise and pitfalls of empowerment evaluation. Setting: The debates occurred at the Claremont Graduate University on August 23-24, 2009. Several hundred evaluators from around the world also viewed and participated in the debates via a live webcast. Intervention: Not applicable. Research Design: Not applicable. Data Collection and Analysis: Not applicable. Findings: Not applicable.